(3efgGL GdHjGf hOSJhQ GdCYjGf aj JQcjH GdCOhjI GdfGaYI ddEfSGfs - (3Gdchgjf GdYWGQ GdGSQGFjdj , OGhO Hf CHj fUQ Hf MaGX, CHh Gdefj,J (B608 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfi QeJ eLehYkG LGeYkG dLejY CZQGVG ade CLO cJGHkG LGeYkG deG QeJg , hdG CbQHGRjf dCMO ef GdeJbOejf Ch GdefJCNQjf cGajkG ajeG bUOJg s
(3BNQgG (B:s
(3ChdkG aChd MaXkG ddbhI heYhfI dQaY GdaVdGJ , fbdJ Pdc Yf Gdabjg CHj ESMGb GdfJWHH hHMU ajg eY GdTjN GdSOjO Hf HjGf ahGab Ydjg hGdg Gdeab Edi GdUhGH s
(3GfXQ CjVkG agQS GdWH HQbe (B" 255"s
(3LeYg dfaSg hdhdOg Sfg (B658 (3hLYdg Ydi NeSI hYTQjf HGHkG JfGhd ajg Ufha GdCOhjI GdeYQhaI ai YUQgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B143s
GAL - (3GdLRA (B1 - (3U (B648 ; GAL - (3GdLRA (B1 - (3U (B897 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B261 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B327 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs